PERSIDANGAN ELEKTRONIK SEBAGAI UPAYA MODERNISASI PERADILAN DI ERA NEW NORMAL - Dewi Asimah (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2021)
Electronic Court (E-court) was arranged by the Supreme Court prior to the Covid-19 pandemic with the issuance of Supreme Court Regulation (hereby refered as “Perma”) No. 3 of 2018 and restrictions with Perma No. 1 of 2019. The application of Electronic Court (E-court) greatly helps the realization of the Vision of the Supreme Court to become a Supreme Indonesian Judiciary Body, which in point 10 is the realization of the Vision of the Supreme Court in the Blueprint is to create a Modern Judiciary Body based on integrated information technology. In the New Normal Era, conventional trials must switch to online trials to prevent Covid-19 based on SEMA No. 1 of 2020. In addition to the many benefits obtained from the implementation of electronic court (e-court), especially during The New Normal Era, there are several obstacle of conducting electronic hearings, such as Electronic proceedings have not yet been regulated in the procedural law because they have only been regulated in a Supreme Court Regulation. Limited facilities and infrastructure, lack of human resources and the trial that was felt to be closed because it was only attended by online parties were also obstacles in electronic litigation.